Euratom research and training in nuclear reactor safety: towards European research and the higher education area. (15th November 2004) - Van Goethem, Georges
In this invited lecture, research and training in nuclear fission are looked at from a European perspective with emphasis on the three success factors of any European policy, namely: common needs, vision and instruments, that ought to be strongly shared amongst the stakeholders across the Member States concerned. As a result, the following questions are addressed: What is driving the current EU trend towards more research, more education and more training, in general? Regarding nuclear fission, in particular, who are the end-users of Euratom "research and training" and what are their expectations from EU programmes? Do all stakeholders share the same vision about European research and training in nuclear fission? What are the instruments proposed by the European Commission (EC) to conduct joint research programmes of common interest for the nuclear fission community? In conclusion, amongst the stakeholders in Europe, there seems to be a wide consensus about common needs and instruments, but not about a common vision regarding nuclear.